The function of web decorations in orb web spiders - Walter, André (Frontiers in Arachnid Science, 2024)
Visual signal, mechanical reinforcement, protein storage, or non-functional stress response? Web decorations constructed by a number of orb web spider species puzzle behavioural ecologists. While some species use a variety of construction materials, it seems particularly difficult to solve the issue for silk decorations. The visual pattern of decoration structures has sparked the researchers’ imagination, and the conclusion that they act as signals is unsurprising. For over a century, however, we have not found a conclusive answer on a specific signal function of silk decorations. More recent studies even suggest that the construction mode of web decorations may render a specific signal function rather unlikely. In this review, I discuss reasons for the continuous struggle to find conclusive answers and what could be alternative routes for unravelling their adaptive significance. Based on my own experience in the field, I present a personal viewpoint, which I hope will be inspiring at a stage where research in this field seems to have reached a dead end. We are faced with a controversial debate, inconclusive and sometimes contradicting results; and an interest in new studies is fading. I draw the attention to three trouble areas, covering research gaps, logical inconsistencies and conceptual misunderstandings. More specifically: 1) Web decorations should be treated more as the dependent variable. 2) Experimental setups of several earlier studies appear flawed in retrospect, and their results thus overinterpreted. 3) We have not understood the evolutionary origin of web decoration. We may look at a signal that is still in an early phase of shaping, and inconclusive results may thus be inevitable. Finally, if web decorations do not act as signals, studies that look for exactly that cannot find conclusive results. In discussing these issues critically, I argue, we can open new routes for progress in finding a satisfying solution of the riddle of the silk decoration function.